FORMATIVE ASSESSMENT IN ENGLISH LEARNING OF JUNIOR HIGH SCHOOL - Dian Fitriani; Bambang A. Loeneto; Rita Inderawati (University of Kuningan, 2021)
Abstract: Formative assessment (assessment-for-learning) helps teachers to conduct teaching and learning activities that can enhance the students’ learning achievement. This study was aimed to find out the teachers’ understanding about formative assessment, the implementation of a formative assessment for English learning including the use of formative assessment to improve the teachers’ teaching and students’ learning, and the supporting and/or hindering factors in implementing a formative assessment. Qualitative in case study design was used in this study. The data were collected through interview, observations, and documentation to four teachers, the school principal, and some observed students as the participants. The data collected were validated through methodological triangulations and were analyzed qualitatively and reported descriptively. The result discovered that teachers’ understanding of formative assessment was in “good” category. The implementation of formative assessment in English learning given by the teachers followed the steps of input, process, and output. The teachers gave follow – up actions namely remedial and enrichment for students although the actions were not carried out as properly as what it is supposed to due to some hindering factors in giving the formative assessment. In conclusion, teachers’ lack of assessment training affects their understanding in implementing formative assessment. Therefore, the teachers need to participate in such a seminar and they need to be given opportunities to join assessment training so that they can get input on how to give assessment well, and moreover to make the right assessment instruments.